Myeloid neoplasms with eosinophilia - Reiter, Andreas; Gotlib, Jason (Blood, 2017)
Molecular diagnostics has generated substantial dividends in dissecting the genetic basis of myeloid neoplasms with eosinophilia. The family of diseases generated by dysregulated fusion tyrosine kinase (TK) genes is recognized by the World Health Organization (WHO) category, “Myeloid/lymphoid neoplasms with eosinophilia and rearrangement of PDGFRA, PDGFRB, or FGFR1, or with PCM1-JAK2.” In addition to myeloproliferative neoplasms (MPN), these patients can present with myelodysplastic syndrome/MPN, as well as de novo or secondary mixed-phenotype leukemias or lymphomas. Eosinophilia is a common, but not invariable, feature of these diseases. The natural history of PDGFRA- and PDGFRB-rearranged neoplasms has been dramatically altered by imatinib. In contrast, patients with FGFR1 and JAK2 fusion TK genes exhibit a more aggressive course and variable sensitivity to current TK inhibitors, and in most cases, long-term disease-free survival may only be achievable with allogeneic hematopoietic stem cell transplantation. Similar poor prognosis outcomes may be observed with rearrangements of FLT3 or ABL1 (eg, both of which commonly partner with ETV6), and further investigation is needed to validate their inclusion in the current WHO-defined group of eosinophilia-associated TK fusion-driven neoplasms. The diagnosis chronic eosinophilic leukemia, not otherwise specified (CEL, NOS) is assigned to patients with MPN with eosinophilia and nonspecific cytogenetic/molecular abnormalities and/or increased myeloblasts. Myeloid mutation panels have identified somatic variants in patients with a provisional diagnosis of hypereosinophilia of undetermined significance, reclassifying some of these cases as eosinophilia-associated neoplasms. Looking forward, one of the many challenges will be how to use the results of molecular profiling to guide prognosis and selection of actionable therapeutic targets.